2017
DOI: 10.3390/rs9080810
|View full text |Cite
|
Sign up to set email alerts
|

Precise Orbit Determination of BeiDou Satellites with Contributions from Chinese National Continuous Operating Reference Stations

Abstract: The precise orbit determination (POD) for BeiDou satellites is usually limited by the insufficient quantity and poor distribution of ground tracking stations. To cope with this problem, this study used the GPS and BeiDou joint POD method based on Chinese national continuous operating reference stations (CNCORS) and IGS/MGEX stations. The results show that the 3D RMS of the differences of overlapping arcs is better than 22 cm for geostationary orbit (GEO) satellites and better than 10 cm for inclined geosynchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The results of such kind of analyses are systematically published in reference to the different orbit models [1,[24][25][26][27][28][49][50][51][52][53][54][55][56][57]. The major innovation introduced by the GOVUS system is the near-real time of calculations and a remarkable ease of repeatability of performed analyses for every user.…”
Section: Assessment Of the Orbit Qualitymentioning
confidence: 99%
“…The results of such kind of analyses are systematically published in reference to the different orbit models [1,[24][25][26][27][28][49][50][51][52][53][54][55][56][57]. The major innovation introduced by the GOVUS system is the near-real time of calculations and a remarkable ease of repeatability of performed analyses for every user.…”
Section: Assessment Of the Orbit Qualitymentioning
confidence: 99%
“…The current result is consistent with the claim that SPDOP is correlated with orbit determination accuracy, thus it can be used as a reference indicator when selecting the distribution design of CORS involved in orbit determination. Chen et al [22] also showed that that there is a correlation between accuracy of orbit determination with the geometry of CORS distribution. They proved that SPDOP has a mild influence on orbit determination for medium earth orbit satellites such as GPS and part of the BeiDou constellation.…”
Section: Spdop Analysismentioning
confidence: 98%
“…This study would recommend a SPDOP upper limit of 4500 for orbit determination using simulated measurement which promises the 3D error to be below 0.01 mm. In a study that uses real measurement, Chen et al [22] showed that cm-level accuracy in orbit determination is achievable with mean SPDOP below 100. On the other hand, Zhang et al [10] result showed that BeiDou satellite with mean SPDOP of 208.6 can have an orbit accuracy of 34cm, the lowest orbit accuracy and second highest mean SPDOP value recorded in that study for middle earth orbit satellites.…”
Section: Spdop Analysismentioning
confidence: 99%
“…Carrier-to-noise ratio (CNR) is defined as the ratio of signal power to the noise power in a unit bandwidth, and is an important indicator for evaluating signal quality in navigation reception [43]. In order to further derive the loss limit of the CNR of the robust ranging algorithm proposed in Section 4.1, the signal energy loss due to the superposition effect of the correlation function is analyzed from the energy perspective of the correlation domain.…”
Section: Analysis Of the Influence Of Adaptive Correction Filter On Cnrmentioning
confidence: 99%